How society’s negative view of videogames can discourage brands from sponsoring eSports - Freitas, Bruno Duarte Abreu (2022)
The purpose of this research was to identify the main motives that contribute to society’s negative view of videogames and that present a risk to the eSports sponsors’ image. To achieve this, an exploratory, qualitative, and integrative literature review was conducted. According to the theoretical data, there are four main reasons why society has a negative perception of videogames. It is commonly believed that: (1) gaming is an unproductive activity, (2) violent videogames incite aggressive behaviors, (3) videogames lead to gaming-addiction, and (4) eSports lead to eSports-related gambling addiction. However, while the literature presents convincing evidence that gaming can create addiction and that eSports can promote gambling addiction, there is no conclusive evidence to assume that violent videogames lead to aggressiveness and there is evidence showing that playing videogames can be a productive activity. Nevertheless, these four beliefs are a threat to the eSports sponsors’ image and may lead them to cancel their existing sponsorships or lead other brands to not want to sponsor eSports to prevent being associated with these negative notions. This research will help expand the minor literature on eSports sponsorships and advance the knowledge of why some eSports sponsorships are terminated and why some brands may be reluctant to sponsor eSports.